Cerebral Venous Sinus Thrombosis: Two Case presentations with different clinical manifestations and multifactorial etiology - Ganeshan, Anusha Skandini; Chango, Angel Alberto Caderon (Open Science Journal, 2017)
Cerebral Venous Sinus Thrombosis (CVST) is a rare form of venous thrombosis which commonly affects young adults. CVST has variable clinical presentation such as headache, seizure, hemiparesis and even coma, thus mimicking stroke and other neurological disorders. Due to such non-specific wide spectrum of clinical presentations and variable etiology in young adults, CVST can be misdiagnosed easily, especially in initial stages of presentation which consequently affects the outcome and prognosis of the patient. Thus when a previously healthy young adults acutely presented with such variable but primarily neurological clinical presentation, it is vital for medical practitioner to have fine knowledge and skills to suspect CVST as a differential diagnosis. We present two cases: first case is a 21 year old female with puerperal CVST who had caesarean section under spinal anaesthesia three weeks before, who presented with headache and recurrent seizures, followed by hemiparesis; the second case is a 25 year old female with CVST, on oral contraceptives, who presented with right monoparesis, aphasia and facial asymmetry. In both cases though CVST was not the initial diagnosis, it was subsequently diagnosed early and confirmed by MRI brain and MRI angiogram and anticoagulation was commenced effectively, despite associated haemorrhagic infarct in the first case. Both patient made remarkable recovery without any significant residual neurological deficit.